2020
DOI: 10.1097/md.0000000000023035
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative therapies for knee osteoarthritis

Abstract: Background: Knee osteoarthritis (KOA) is a degenerative disease, making a unique contribution to chronic pain, edema, and limited mobility of knee joint. This disease is an important factor affecting the quality of life of middle-aged and elderly people. Complementary and alternative medicine (CAM) therapies have been used clinically to treat KOA; however, the selection strategies of different CAM interventions in clinical practice are still uncertain, and the purpose of this study is to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Currently, cartilage protection still awaits a dedicated pharmaceutical solution. This has prompted interest in complementary and alternative medicine [ 16 , 17 ], including nutraceuticals and herbal remedies believed to possess chondroprotective effects and the ability to stimulate cartilage repair [ 18 , 19 ]. The exploration of traditional medicinal systems for potential drugs aiming at reducing inflammation, safeguarding cartilage, enhancing joint functionality, and reinstating activity levels has become a topic of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cartilage protection still awaits a dedicated pharmaceutical solution. This has prompted interest in complementary and alternative medicine [ 16 , 17 ], including nutraceuticals and herbal remedies believed to possess chondroprotective effects and the ability to stimulate cartilage repair [ 18 , 19 ]. The exploration of traditional medicinal systems for potential drugs aiming at reducing inflammation, safeguarding cartilage, enhancing joint functionality, and reinstating activity levels has become a topic of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…4 Owing to the side effects associated with the use of pharmacological management of OA, 5 there has been a major shift in the use of Complementary and Alternative Medicine (CAM) therapies. 6,7 Few studies [8][9][10][11] suggested homeopathy to be effective in the management of OA but no such definitive conclusion could be made. In this regard, a randomised placebo-controlled trial was conducted to assess the efficacy of individualised homeopathic medicines in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the escalation in the number of cases of osteoarthritis today, even with advanced medical technology, this research study aims to gather information about every aspect of the topic of interest [ 3 , 4 ]. Along with surgeries, an alternative approach for the treatment of osteoarthritis was the focus of this research for the benefit of public health globally [ 5 , 6 ]. Bibliometric analysis is one such tool where qualitative and quantitative statistical analysis of all the articles and of all types, is carried out [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%